2 - Student Loans: Potential, Problems, and Lessons from International Experience: Maureen Woodhall - Maureen Woodhall, (Journal of Higher Education in Africa, 2004)
This article, prepared for a conference on Financing Higher Education: Diversify- ing Revenue and Expanding Accessibility held in Dar-es-Salaam in March 2001, draws on a wide range of experience throughout the developing world to inform policies attempting to create student loans programs in Africa. It outlines problems common to student loan programs (most of which, in Africa, have not been suc- cessful), ranging from inadequate capital to excessive subsidization to the inability to surmount political opposition to loans. There are several key policy decisions, answers to which will largely determine the possible recovery rate but which will also determine the accessibility of the program to students and may also affect the likely political receptivity to the idea of loans. The article concludes that loan pro- grams can be designed to be more effective and efficient and thus to contribute revenue diversification in Africa.